2019
DOI: 10.1016/j.cryobiol.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

First birth of a healthy infant following intra-cytoplasmic sperm injection using a new permeable cryoprotectant-free sperm vitrification protocol

Abstract: First birth of a healthy infant following intra-cytoplasmic sperm injection using a new permeable cryoprotectant-free sperm vitrification protocol, Cryobiology (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This method can be applied in all techniques of in vitro fertilization in reproductive medicine programs including epididymal (MESA) and testicular (TESE) spermatozoa 18,46 …”
Section: Applications Of the Vitrification Methods In Human Medicinementioning
confidence: 99%
See 3 more Smart Citations
“…This method can be applied in all techniques of in vitro fertilization in reproductive medicine programs including epididymal (MESA) and testicular (TESE) spermatozoa 18,46 …”
Section: Applications Of the Vitrification Methods In Human Medicinementioning
confidence: 99%
“…17,34,54 This method can be applied in all techniques of in vitro fertilization in reproductive medicine programs including epididymal (MESA) and testicular (TESE) spermatozoa. 18,46 Our group has shown that not only is motility properly preserved, as well as DNA integrity and membranes. 13,55 In addition,…”
Section: Applic Ations Of the Vitrific Ation Me Thod In H Uman Med mentioning
confidence: 99%
See 2 more Smart Citations
“…Live births were achieved with vitrified spermatozoa by intracytoplasmic sperm injection (ICSI) [8] and by intrauterine insemination [9]. A healthy birth using a vitrified sperm sample was recently reported in Spain after a Day 5 blastocyst was monitored and transferred [10].…”
Section: Introductionmentioning
confidence: 99%